Does Climate Change Matters? Perspective Of Major Cities In Malaysia - Rose Aida, Othman (Universiti Malaysia Sarawak, (UNIMAS), 2013)
This study attempts to examine the impact of climate change toward economic growth in perspective of major cities in Malaysia for the period 1980-2010. Augmented Dickey-Fuller (ADF) unit root test, Johansen and Juselius cointegration test and Vector Error Correction modelling to examine the relationship between variable under the study. The results show that in different major cities show in different results. By using Johansen and Juselius Cointegration test, the results indicated that long run relationship exists between the variables for all major cities except Kuala Terengganu. The evidence also indicate that mean maximum temperature have positive impact on the economic growth in Subang and Kuching. The mean minimum temperature have negative impact on the economic growth in Kuala Terengganu, Kuching and Kota Kinabalu. Finally, rainfall has a negative impact on the economic growth for all major cities in Malaysia. As a whole, the government should commit to ensuring that society is adapting to the effects of climate change.